2007
DOI: 10.1093/eurheartj/ehm508
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of operator radiation exposure with optimized radiation protection devices during coronary angiograms and ad hoc percutaneous coronary interventions by radial and femoral routes

Abstract: Although the radial route decreases peripheral arterial complication rates, increased radiation exposure of operators despite extensive use of specific protection devices is currently a growing problem for the interventional cardiologist health. Radial route indication should be promptly reconsidered in the light of the present findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
4
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(93 citation statements)
references
References 14 publications
6
79
4
4
Order By: Relevance
“…In our study, significantly high fluoroscopy time of r-CA and r-PCI groups is consistent with previous studies (9,21,22). It may be argued that mean fluoroscopy time of f-CA as well as r-CA is relatively high.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, significantly high fluoroscopy time of r-CA and r-PCI groups is consistent with previous studies (9,21,22). It may be argued that mean fluoroscopy time of f-CA as well as r-CA is relatively high.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that increased operator radiation exposure during radial access, as opposed to femoral access, is related to increase in FT, reflecting technical difficulties and to the slightly closer operator's position to the x-ray tube and to the patient, compared with femoral access. 5,15,16 In contrast, decreased operator radiation dose and shorter FT have been reported when using LRA compared with RRA. 10,11,17e20 In our study, there are some details in radiation protection techniques that should be taken into consideration: First, during RRA procedures, the leaded glass mobile panel is positioned less proximally to the table compared with LRA and RFA to facilitate the right radial access.…”
Section: Discussionmentioning
confidence: 99%
“…18 More importantly, a significant amount of radiation scatter from the patients' pelvic bone structures should not be overlooked. 19 Another limitation that cannot be ignored is the small patient population. A larger sample of patients is needed to strengthen the statistical power of this study.…”
Section: Discussionmentioning
confidence: 99%